MANAGEMENT, DISTRIBUTION, AND REDEMPTION OF VILLAGE FUND - Amalia Diamantina (Fakultas Hukum, Universitas Diponegoro, 2017)
One on the policies following the change of politics of law in village management is the allocation of Village Fund in the state budget. The management, distribution, and redemption of Village Fund, as well as the obstacles and how to overcome the problems were studied. The research method used was normative. The distribution and redemption arrangements of Village Fund were related to the coordination and communication of three Ministries, Regency / City and Village, village assistants, the requirements of administration and finance, and human resource capacity. The obstacles in the management, distribution, and redemption of Village Fund were that the requirements in the management and the coordination of distribution and redemption of Village Fund have not been met by villages and the villages lacked of preparation. It was overcome by the harmonization of legislation, improved coordination, acceleration of compliance, and increase in the capacity of village officials